27th Bilateral Symposium Poznan-Halle Rare diseases in clinical practice (Journal of Medical Science, 2018)
As part of long-term bilateral cooperation with Martin Luther University in Halle, the 27th Bilateral Symposium Poznań-Halle "Rare diseases in clinical practice" was held on December 16. The participants of the symposium included research workers of both partner universities. On this occasion, talks were held to set up research groups that will carry out joint activities in the field of science and research and the first Poznań-Halle groups were tentatively established. Presentation of prizes for the best oral and poster presentations is a long-standing tradition of the symposium. This award is named after two Professors: Prof. Zeige and Prof. Hasik, who initiated cooperation between our Universities over 30 years ago. In the current edition of the symposium the first prize, two second prizes and two third prizes were given. To add, two representatives of our university were honored. The first prize went to Krzysztof Piersiała, a 6th year student of the First Medical Faculty I and the deputy chairman of the Student Scientific Club at the Clinic of Otolaryngology and Laryngological Oncology. The awarded work was written under the supervison of Prof. Małgorzata Wierzbicka, who is the Head of the Clinic and Joanna Jackowska M.D., Ph.D. The third prize went to Dr Michał Prendecki, who is preparing a doctoral dissertation at PUMS Department and Clinic of Neurology (Head: Prof. Wojciech Kozubski). The work presented at the symposium was prepared in the Laboratory of Neurobiology and supervised by Prof. Jolanta Dorszewska, who tutors Dr Prendecki’s doctoral thesis.